Transnasal humidified rapid insufflation ventilatory exchange (THRIVE): A game changer in apnoeic anaesthesia for shared airway procedures – A retrospective study - Minal Harde; Manish Patil; Anjana Sahu; Charulata Deshpande; R Akhilnath; Kalpesh Pawara (Indian Journal of Anaesthesia)
Background and Aims: Transnasal humidified rapid insufflation ventilatory exchange (THRIVE) is a valuable adjunct during apnoea. Conventional techniques of apnoeic anaesthesia have limitations. THRIVE helps to maintain oxygenation during the apnoeic periods in tubeless airway surgeries. We aimed to evaluate tubeless apnoeic anaesthesia in shared airways using THRIVE to determine safe apnoea time. Methods: Two years of retrospective data were collected at a tertiary care centre, which included 60 patients in whom THRIVE was used for apnoeic anaesthesia. We appraised tubeless apnoeic anaesthesia in shared airways using THRIVE to determine safe apnoea time. Data on oxygenation, haemodynamic parameters, ventilation and the perioperative course were also collected. The data were analysed using GNU PSPP 1.0.1 software. Results: The patients’ mean age was 48.53 [standard deviation (SD):16.62] years. Microlaryngoscopy [24 (40%)], rigid bronchoscopy [12 (20%)], tracheal dilatation [12 (20%)] and foreign body removal [8 (13.3%)] were the common procedures. The mean apnoea time was 14.5 (SD: 2.05) min. Patients maintained normal haemodynamic parameters, with a mean oxygen saturation of 98% during apnoea. The highest mean end-tidal carbon dioxide at the end of apnoea was 55 mmHg, which normalised after 1–2 min of ventilation. Intermittent ventilation was done in eight patients as the apnoea time exceeded 20 min. Emergence and recovery were smooth, and none of the patients developed any complications throughout the procedure. Conclusion: THRIVE can be effectively and safely used for tubeless apnoeic anaesthesia, with an uninterrupted apnoea time of approximately 15 min without complications.